Vitamins B1, B6, and B12 and Peripheral Neuropathies: International expert consensus: Vitaminas B1, B6, B12 y Neuropatías Periféricas. Consenso de expertos. - Longa López, John (2024)
Based on a bibliographic review of the literature, a consensus of international experts has been carried out on the use of vitamins B1, B6, B12, in their deficiencies, and in the peripheral neuropathy that may be associated with them, to optimize the management of these conditions. Several questions considered important and worthy of being addressed and clarified were raised, retaining nine of them for further discussion to achieve consensus. Forty one recommendations on the management of these conditions have been proposed, with unanimity of the participants in the consensus. This has been an attempt to clarify controversial points, assisting the clinician's attitude in current medical practice.